2021
DOI: 10.1002/aesr.202000065
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Reorientation and Amorphization Induced by Stressing Efficient and Stable P–I–N Vacuum‐Processed MAPbI3 Perovskite Solar Cells

Abstract: Herein, the long‐term stability of vacuum‐deposited methylammonium lead iodide (MAPbI3) perovskite solar cells (PSCs) with power conversion efficiencies (PCEs) of around 19% is evaluated. A low‐temperature atomic layer deposition (ALD) Al2O3 coating is developed and used to protect the MAPbI3 layers and the solar cells from environmental agents. The ALD encapsulation enables the MAPbI3 to be exposed to temperatures as high as 150 °C for several hours without change in color. It also improves the thermal stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 73 publications
(99 reference statements)
0
34
0
Order By: Relevance
“…These semitransparent PSCs with PLD‐ITO deposited at 0.033 mbar were tested under illumination from both sides, either from the glass or from the PLD‐ITO top contact (device samples were encapsulated by 30 nm of Al 2 O 3 deposited by atomic layer deposition, as described in our previous publication). [ 53 ] As shown in Figure 6D, both J – V curves are very similar. Our ongoing investigation is on elucidating the differences between top and bottom illumination of both p‐i‐n and n‐i‐p configurations.…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…These semitransparent PSCs with PLD‐ITO deposited at 0.033 mbar were tested under illumination from both sides, either from the glass or from the PLD‐ITO top contact (device samples were encapsulated by 30 nm of Al 2 O 3 deposited by atomic layer deposition, as described in our previous publication). [ 53 ] As shown in Figure 6D, both J – V curves are very similar. Our ongoing investigation is on elucidating the differences between top and bottom illumination of both p‐i‐n and n‐i‐p configurations.…”
Section: Resultsmentioning
confidence: 61%
“…The devices were encapsulated using atomic layer deposition of Al 2 O 3 at 40 °C, using a protocol recently published by us. [53] General Characterization: Absorption spectra were collected using a fiber optics-based Avantes Avaspec2048 spectrometer. X-ray photoelectron spectra of sample surfaces were recorded using a Thermo Scientific K-Alpha with a monochromatic Al Kα X-ray source (1486.6 eV) available in the ICMol facilities; data were analyzed and deconvoluted with Avantage software; the binding energies were adjusted to the standard C 1s peak at 284.6 eV.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to the characterization, the stacks were encapsulated using atomic layer deposition for the deposition of a transparent Al 2 O 3 (30 nm) film at 40 1C to prevent possible degradation from ambient conditions. 55…”
Section: Device Fabricationmentioning
confidence: 99%
“…[1][2][3][4] However, long-term ambient instability and thermal instability still remains the most critical issues to be resolved for successful commercialization of this technology. 5,6 Since a typical high performance PSC device has a relatively simple device structure consisting of a perovskite active layer sandwiched between charge transporting layers (i.e., the electron transporting layer (ETL) and hole transporting layer (HTL)), device instability is generally associated with a degradation in these layers under various internal/external factors such as humidity, temperature, oxygen, UV illumination, and ion diffusion. [7][8][9][10][11][12] Recent studies have demonstrated that organic HTL materials could play a considerable role in the stability of n-i-p PSCs by forming a top protective layer (i.e., physical barrier against various ambient species) on the perovskite active lm.…”
Section: Introductionmentioning
confidence: 99%